The regulatory effects of maize saving irrigation in arid region - Zhao, Yuhao; Li, Xin; Lin, Meiwei; Gao, Chen; Li, Xiaoya; Wu, Kunkun; He, Liang; Sun, Weihong (Frontiers in Plant Science, 2025)
The increased drought stress caused by worldwide climate-change-driven aridification has exacerbated water scarcity in agricultural production, posing a significant challenge to agricultural sustainability. This study was conducted at Huaxing Farm in Changji City, Xinjiang, establishing five irrigation gradients: 100% (CK), 90% (W1), 80% (W2), 70% (W3), and 60% (W4) of the conventional water supply (full irrigation requirement). The primary objective was to systematically investigate the effects of water regulation on physiological and biochemical parameters, yield formation, and kernel quality in maize plants. A multidimensional TOPSIS-entropy weight method was used to evaluate the effectiveness of these irrigation treatments in the context of drought adaptation. The results indicated that moderate regulated deficit irrigation (W1) increased yield by 8.0% while using 10% less water. This treatment also led to higher protein levels (7.59g/100g) and starch content (68.1g/100g). In contrast, severe regulated deficit irrigation (W4) failed to alleviate drought stress, which significantly induced biomass loss and inhibited yield formation. A comprehensive review revealed that W1 was the top-performing treatment, achieving the highest overall evaluation index of 0.728. W1 activated a synergistic mechanism that combined osmotic adjustment and antioxidant defense. This specific physiological adaptation was characterized by elevated proline accumulation, activation of key enzyme systems, and stabilization of malondialdehyde levels, which indicated effective mitigation of drought-induced cellular damage. This physiological optimization improved photoassimilate partitioning to the kernels. Therefore, W1 represented a promising irrigation strategy, providing insights into the physiological basis for synergistic stress resistance triggered by moderate water deficit and enabling yield gains with 10% less irrigation.